Adipocyte-specific inactivation of Acyl-CoA synthetase fatty acid transport protein 4 (Fatp4) in mice causes adipose hypertrophy and alterations in metabolism of complex lipids under high fat diet - Lenz, Lena-Solveig; Marx, Jana Corinna; Chamulitrat, Walee; Kaiser, Iris; Gröne, Hermann-Josef; Liebisch, Gerhard; Schmitz, Gerd; Elsing, Christoph; Straub, Beate Katharina; Füllekrug, Joachim; Stremmel, Wolfgang; Herrmann, Thomas (The journal of biological chemistry, 2011)
Fatp4 exhibits acyl-CoA synthetase activity and is thereby able to catalyze the activation of fatty acids for further metabolism. However, its actual function in most tissues remains unresolved, and its role in cellular fatty acid uptake is still controversial. To characterize Fatp4 functions in adipocytes in vivo, we generated a mouse line with adipocyte-specific inactivation of the Fatp4 gene (Fatp4A−/−). Under standard conditions mutant mice showed no phenotypical aberrance. Uptake of radiolabeled palmitic and lignoceric acid into adipose tissue of Fatp4A−/− mice was unchanged. When exposed to a diet enriched in long chain fatty acids, Fatp4A−/− mice gained more body weight compared with control mice, although they were not consuming more food. Pronounced obesity was accompanied by a thicker layer of subcutaneous fat and greater adipocyte circumference, although expression of genes involved in de novo lipogenesis was not changed. However, the increase in total fat mass was contrasted by a significant decrease in various phospholipids, sphingomyelin, and cholesteryl esters in adipocytes. Livers of Fatp4-deficient animals under a high fat diet exhibited a higher degree of fatty degeneration. Nonetheless, no evidence for changes in insulin sensitivity and adipose inflammation was found. In summary, the results of this study confirm that Fatp4 is not crucial for fatty acid uptake into adipocytes. Instead, under the condition of a diet enriched in long chain fatty acids, adipocyte-specific Fatp4 deficiency results in adipose hypertrophy and profound alterations in the metabolism of complex lipids.
Gesehen am 17.08.2022